2018
DOI: 10.1016/j.labeco.2018.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The intergenerational transfer of the employment gender gap

Abstract: Despite well-documented convergence during the later years of the 20 th century, labor market attachment remains markedly higher for men than for women. The current paper employs rich longitudinal registry data to investigate the intergenerational transfer of the gender gap in employment. We explore the extent that family-and community-level characteristics, measured in childhood, differentially predict employment for adult Norwegian men and women. Drawing on theories pertaining to the importance of informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…In line with Farré and Vella (2013) and Haaland et al (2018), our results suggest that gender role attitudes are persistent across generations: the greater gender inequality in housework (i.e., a higher value for the mother to father share of housework) is in parents' households, the greater it is in children's own families, with a slightly larger coefficient for sons. The amount of domestic work performed during childhood and the overall amount of domestic work in the family of origin are not relevant in explaining the gender distribution of domestic work in children's own families.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In line with Farré and Vella (2013) and Haaland et al (2018), our results suggest that gender role attitudes are persistent across generations: the greater gender inequality in housework (i.e., a higher value for the mother to father share of housework) is in parents' households, the greater it is in children's own families, with a slightly larger coefficient for sons. The amount of domestic work performed during childhood and the overall amount of domestic work in the family of origin are not relevant in explaining the gender distribution of domestic work in children's own families.…”
Section: Introductionsupporting
confidence: 75%
“…However, empirical evidence with direct observation of parents and children behaviour related to gender role attitudes is scarce. For instance, Farré and Vella (2013) and Haaland et al (2018) found that cultural attitudes regarding the role of women in the family and labour market are transmitted across generations. Farré and Vella (2013) based their results on individuals' opinions towards gender roles, finding that the mother's view of the role of women in the labour market and the family is strongly correlated with the views of her sons and daughters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25. The spatial distribution of gender norms in Norway is discussed in Haaland et al (2013). They use the regional distribution of support for the Christian Democratic Party ('Kristelig Folkeparti') in elections as a proxy for traditional gender norms.…”
Section: Notesmentioning
confidence: 99%
“…Ethnicity is also an important contributor to the gender wage gap, since non-white workers are more likely than white workers to receive lower wages (Mandel & Semyonov, 2016). Many studies include additional factors, such as the extent of risk preferences (Jung et al, 2018), country-specific policies (Christofides, Polycarpou, & Vrachimis, 2013) and intergenerational transfer of gender norms (Haaland, Rege, Telle, & Votruba, 2018), to explain why labour market outcomes differ. However, when differences in all relevant and available characteristics are taken into account, there may still be an unexplained differential in employment or wages.…”
Section: Literature Reviewmentioning
confidence: 99%